Stress and Inflammation in Coronary Artery Disease: A Review Psychoneuroendocrineimmunology-Based - Fioranelli, Massimo; Bottaccioli, Anna G.; Bottaccioli, Francesco; Bianchi, Maria; Rovesti, Miriam; Roccia, Maria G. (Frontiers in Immunology, 2018)
Recent findings have deeply changed the current view of coronary heart disease, going beyond the simplistic model of atherosclerosis as a passive process involving cholesterol build-up in the subintimal space of the arteries until their final occlusion and/or thrombosis and instead focusing on the key roles of inflammation and the immune system in plaque formation and destabilization. Chronic inflammation is a typical hallmark of cardiac disease, worsening outcomes irrespective of serum cholesterol levels. Low-grade chronic inflammation correlates with higher incidence of several non-cardiac diseases, including depression, and chronic depression is now listed among the most important cardiovascular risk factors for poor prognosis among patients with myocardial infarction. In this review, we include recent evidence describing the immune and endocrine properties of the heart and their critical roles in acute ischaemic damage and in post-infarct myocardial remodelling. The importance of the central and autonomic regulation of cardiac functions, namely, the neuro-cardiac axis, is extensively explained, highlighting the roles of acute and chronic stress, circadian rhythms, emotions and the social environment in triggering acute cardiac events and worsening heart function and metabolism in chronic cardiovascular diseases. We have also included specific sections related to stress-induced myocardial ischaemia measurements and stress cardiomyopathy. The complex network of reciprocal interconnections between the heart and the main biological systems we have presented in this paper provides a new vision of cardiovascular science based on psychoneuroendocrineimmunology.